2000
DOI: 10.1021/jm000018k
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamic Acid Derivatives as Potent Peptide Deformylase Inhibitors and Antibacterial Agents

Abstract: Low-molecular-weight beta-sulfonyl- and beta-sulfinylhydroxamic acid derivatives have been synthesized and found to be potent inhibitors of Escherichia coli peptide deformylase (PDF). Most of the compounds synthesized and tested displayed antibacterial activities that cover several pathogens found in respiratory tract infections, including Chlamydia pneumoniae, Mycoplasma pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. The potential of these compounds as antibacterial agents is discussed with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
78
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…PDF inhibitors therefore represent a new type of antibacterial agent with a novel mode of action and provide an alternative for the treatment of hospitalized patients with CAP and SSSIs caused by pathogens resistant to current therapies. The design of PDF inhibitors for potential clinical use has been the subject of research in a number of laboratories over the past decade, partly inspired by the discovery that actinonin, a naturally occurring antibacterial agent, is an inhibitor of PDF (18,19). A large number of chemically diverse PDF inhibitors have been discovered through these efforts, and compounds with good antibacterial activity and in vivo efficacy have been reported (20).…”
mentioning
confidence: 99%
“…PDF inhibitors therefore represent a new type of antibacterial agent with a novel mode of action and provide an alternative for the treatment of hospitalized patients with CAP and SSSIs caused by pathogens resistant to current therapies. The design of PDF inhibitors for potential clinical use has been the subject of research in a number of laboratories over the past decade, partly inspired by the discovery that actinonin, a naturally occurring antibacterial agent, is an inhibitor of PDF (18,19). A large number of chemically diverse PDF inhibitors have been discovered through these efforts, and compounds with good antibacterial activity and in vivo efficacy have been reported (20).…”
mentioning
confidence: 99%
“…However, recently it has been shown that the natural antibiotic actinonin, a hydroxamic acid pseudopeptide, is a potent inhibitor of PDF (11). In addition, a series of ␤-sulfonyl and ␤-sulfinylhydroxamic acid derivatives have been shown to be potent PDF inhibitors with in vitro antibacterial activity (1). As a result of our previous experience with mammalian matrix metalloproteinases (6), we have accumulated an extensive library of potential metalloenzyme inhibitors.…”
mentioning
confidence: 99%
“…This highthroughput standard assay is based on the measurement of the hydrolysis of formyl-methionine-alanine-serine (f-MAS; K m , 4 to 10 mM) by recombinant purified E. coli PDF via detection of the formation of the new free amino group of MAS by reaction with fluorescamine (2). To further characterize the compounds, a PDF-specific TC-TL assay was developed that simulates the physiological conditions much better than the assay with the isolated enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently described the identification, optimization, and biological characterization of new PDF inhibitors (2). Since the antibacterial activities of these inhibitors were lower than expected from the inhibition at the enzyme level, we have performed several studies in order to better understand this discrepancy (3).…”
mentioning
confidence: 99%